Examining the Subjective Reasons Leading to Disparities in Academic Achievement among Students in the Architectural Design course at the University of Tripoli. : Case study: Architectural Design Students - M. Shibub , Mariam (Scientific Journal of University of Benghazi, 2024)
Architectural education plays a vital role in developing and advancing the urban structure and raising the level of performance of technical departments to achieve a better standard of living for the country’s people within international standards. Architectural design is considered one of the most important basic subjects in the crystallization and formation of an architect's personality. Therefore, the disparity and sometimes weakness of the scientific achievement of students in the Department of Architecture in this subject undoubtedly leads to the inability of graduates to contribute to the process of construction effectively in practical life. This research aims to find out the reasons for the disparity in educational achievement among students of the architectural design subject in the Department of Architecture and Urban Planning at the University of Tripoli. The Descriptive Analytical method was employed to identify key challenges hindering students' educational progress in architectural design courses AR 302 and AR 403. The study examined a sample that comprised over 25% of the students across the two courses. The results were that all reasons for lack of achievement related to the students themselves. They were represented in order and according to importance in the degree of intelligence; hobbies; method of reading; access to books and references and the extent of benefiting from them; and attention and concentration during lectures. The study found that students did not have the moral courage to answer questions due to shyness (91.7%) and fear of the professor (8.3%). The research resulted in a set of recommendations, the most important of which is that professors should invest in the first meeting with students when presenting the course program. The study also recommends professors provide students with advice and guidance in developing their IQ, aim to reduce or eradicate the effects of shyness, and encourage and motivate students to participate in discussions and ask questions. Implementation of these recommendations will increase the likelihood of fostering an integrated educational institution that is constructive and capable of graduating confident scientific cadres.